2018
DOI: 10.3390/en11123518
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Combustion of a Methane Hydrate Layer Using Thermal Imaging and Particle Tracking Velocimetry Methods

Abstract: In this paper, the combustion of methane hydrate over a powder layer is experimentally studied using thermal imaging and Particle Tracking Velocimetry (PTV) methods. The experiments are carried out at different velocities of the external laminar air-flow from zero to 0.6 m/s. Usually, simulation of methane hydrate combustion is carried out without taking into account free convection. A standard laminar boundary layer is often considered for simplification, and the temperature measurements are carried out only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Traditionally, this technique is widely used to study small-scale flows (Azadi and Nobes [149]) and to low-particle density flows (Cornic et al [150]) but recently its use has also been expanded to large-scale indoor airflows (Fu et al [151]) and to the investigation of the near-wall regions (Fu et al [152]). Further recent studies used PTV to study the combustion of methane hydrate over a powder layer (Misyura et al [153]), the activation of the low reactivity industrial fuel (Egorov et al [154]), the effect of highspeed jets in highly abrasive environments (Riha et al [155]), and velocity measurements in porous media (Sabbagh et al [156]). In recent years, the evolution of PTV has mainly concerned technological and algorithmic development, leading to the definition of 3DPTV and 4DPTV.…”
Section: Digital Image Analysis (Dia) Techniquesmentioning
confidence: 99%
“…Traditionally, this technique is widely used to study small-scale flows (Azadi and Nobes [149]) and to low-particle density flows (Cornic et al [150]) but recently its use has also been expanded to large-scale indoor airflows (Fu et al [151]) and to the investigation of the near-wall regions (Fu et al [152]). Further recent studies used PTV to study the combustion of methane hydrate over a powder layer (Misyura et al [153]), the activation of the low reactivity industrial fuel (Egorov et al [154]), the effect of highspeed jets in highly abrasive environments (Riha et al [155]), and velocity measurements in porous media (Sabbagh et al [156]). In recent years, the evolution of PTV has mainly concerned technological and algorithmic development, leading to the definition of 3DPTV and 4DPTV.…”
Section: Digital Image Analysis (Dia) Techniquesmentioning
confidence: 99%
“…However, existing processes still require the external transportation of fuel and oxidizers into the combustion heat exchanger, involving on-site fuel storage and injection, which increases technical complexity and costs. By conducting combustion experiments on methane hydrates, scholars [18][19][20][21] have found that the energy transfer between the combustion flame and the hydrate decomposition products is uneven and unstable. Direct combustion of natural gas hydrates leads to lower flame temperatures and lower combustion efficiency [22,23].…”
Section: Introductionmentioning
confidence: 99%